2015
DOI: 10.1016/j.taap.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in murine hepatic transcriptional and proteomic responses to TCDD

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is an environmental contaminant that produces myriad toxicities in most mammals. In rodents alone, there is a huge divergence in the toxicological response across species, as well as among different strains within a species. But there are also significant differences between males and females animals of a single strain. These differences are inconsistent across model systems: the severity of toxicity is greater in female rats than males, while male mice and guinea pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 69 publications
3
33
0
Order By: Relevance
“…An additional four of these genes had differential RNA abundance in at least two groups: Cyp1a2 in C57BL/6 and DBA/2 (borderline significant (log 2 fold change = 0.99) in rWT) and Fmo3 , Nqo1 and Ugt1a9 only in the TCDD-sensitive cohorts. Inmt shows significant repression in only rWT at this early time point, while Aldh3a1 shows no response in mice (consistent with previous studies [29,37,38]). We next examined sets of genes which demonstrated altered RNA abundance in the TCDD-resistant DBA/2 mouse liver or TCDD-sensitive cohorts (Fig 2D-E).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…An additional four of these genes had differential RNA abundance in at least two groups: Cyp1a2 in C57BL/6 and DBA/2 (borderline significant (log 2 fold change = 0.99) in rWT) and Fmo3 , Nqo1 and Ugt1a9 only in the TCDD-sensitive cohorts. Inmt shows significant repression in only rWT at this early time point, while Aldh3a1 shows no response in mice (consistent with previous studies [29,37,38]). We next examined sets of genes which demonstrated altered RNA abundance in the TCDD-resistant DBA/2 mouse liver or TCDD-sensitive cohorts (Fig 2D-E).…”
Section: Resultssupporting
confidence: 92%
“…Previous studies observed transcriptomic changes as early as 6 hours in C57BL/6 mouse liver [29] and 19 hours in rat liver [21,23,30] following exposure to TCDD. To further study the role that the Ahr has in ‘early onset’ changes, we identified genes with significant differential mRNA abundance following a dose of 5 or 500 μg/kg TCDD in sensitive mouse strains (C57BL/6 or rWT) or resistant (DBA/2) mouse strains.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental design, animal handling and sample preparation for individual experiments are described elsewhere [34, 3743]. Data from human Multipotent Adipose-Derived Stem (hMADS) cells (differentiated and undifferentiated; TCDD treated and control) were downloaded from NCBI’s GEO repository (GSE32026) [42], as were data for primary human and female Sprague–Dawley (SD) rat hepatocyte cell lines (GSE14555) [44].…”
Section: Methodsmentioning
confidence: 99%
“…RNA isolation and microarray hybridization were performed as described elsewhere [37, 38, 46]. Remaining data were generated and deposited in the GEO repository as described in the original publications [34, 3741, 43]. …”
Section: Methodsmentioning
confidence: 99%
“…This is a significant limitation for the ability to translate results from cell culture studies, in which incubations were performed only with the parent compounds, to the in vivo situation. Moreover, it has to be pointed that there are large sex‐related (Mugford and Kedderis, ; Renaud et al., ; Liu et al., ; Ruiz et al., ; Dellinger et al., ; Prokopec et al., ) and species‐dependent (Matal et al., ; Yamazaki et al., ; Helke and Swindle, ; Saengtienchai et al., ) differences in xenobiotic metabolism which largely explains that the spectrum of polyphenol metabolites, their tissue distribution and concentrations in blood following ingestion of polyphenols or polyphenol mixtures can differ markedly between species and between males and females (Weinert et al., ; Margalef et al., ). This is a clear hindrance for the ability to transfer data from male‐to‐female animals and from one species to another one.…”
Section: Potential Of Plant Polyphenols To Combat Oxidative Stress Anmentioning
confidence: 99%